2023
DOI: 10.3390/membranes13030253
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of UiO-66 on Hollow Fibre Membrane for Membrane Distillation

Abstract: The hydrophobicity of metal–organic frameworks (MOFs) is critical in enhancing the separation process in membrane distillation. Herein, a new superhydrophobic University of Oslo 66 (UiO-66) MOFs was successfully constructed on the top of alumina hollow fibre (AHF) membrane for desalination purposes. The fabrication methodology of the membrane involved in situ growth of pure crystalline UiO-66 on top of AHF and post-synthetic modification by fluorosilane grafting. The resultant membrane was characterised to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…In this case, the functional groups' physico-chemical properties determined the differences in droplet and bril dimensions (Table 2). Measuring zeta potential and contact angle revealed that UiO-66-NH 2 had the highest contact angle and, thus, the greatest hydrophobicity, and UiO-66-(COOH) 2 had the highest zeta potential [35][36][37][38].…”
Section: Zeta Potential and Contact Angels' Resultsmentioning
confidence: 99%
“…In this case, the functional groups' physico-chemical properties determined the differences in droplet and bril dimensions (Table 2). Measuring zeta potential and contact angle revealed that UiO-66-NH 2 had the highest contact angle and, thus, the greatest hydrophobicity, and UiO-66-(COOH) 2 had the highest zeta potential [35][36][37][38].…”
Section: Zeta Potential and Contact Angels' Resultsmentioning
confidence: 99%